The diversity of Polychaeta in the Kaca-kacu waters of the Pulau Nasi, Aceh Besar district - Sarah Nadia; Ali Sarong; Ismul Huda; Mimie Saputri; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
This study is entitled